Characterization of HA-tagged α9 and α10 nAChRs in the mouse cochlea - Pankhuri Vyas (Nature Portfolio, 2020)
Abstract Neurons of the medial olivary complex inhibit cochlear hair cells through the activation of α9α10-containing nicotinic acetylcholine receptors (nAChRs). Efforts to study the localization of these proteins have been hampered by the absence of reliable antibodies. To overcome this obstacle, CRISPR-Cas9 gene editing was used to generate mice in which a hemagglutinin tag (HA) was attached to the C-terminus of either α9 or α10 proteins. Immunodetection of the HA tag on either subunit in the organ of Corti of adult mice revealed immunopuncta clustered at the synaptic pole of outer hair cells. These puncta were juxtaposed to immunolabeled presynaptic efferent terminals. HA immunopuncta also occurred in inner hair cells of pre-hearing (P7) but not in adult mice. These immunolabeling patterns were similar for both homozygous and heterozygous mice. All HA-tagged genotypes had auditory brainstem responses not significantly different from those of wild type littermates. The activation of efferent neurons in heterozygous mice evoked biphasic postsynaptic currents not significantly different from those of wild type hair cells. However, efferent synaptic responses were significantly smaller and less frequent in the homozygous mice. We show that HA-tagged nAChRs introduced in the mouse by a CRISPR knock-in are regulated and expressed like the native protein, and in the heterozygous condition mediate normal synaptic function. The animals thus generated have clear advantages for localization studies.